2004
DOI: 10.1007/s10562-004-7920-x
|View full text |Cite
|
Sign up to set email alerts
|

Unusual Forms of Molecular Hydrogen Adsorption by Cu+1 Ions in the Copper-Modified ZSM-5 Zeolite

Abstract: DRIFT and IR transmittance spectra of H 2 adsorbed at 77 K or at room temperature by the copper-modified ZSM-5 zeolite pre-evacuated or pre-reduced in CO at 873 K indicated several unusual forms of adsorbed hydrogen. H-H stretching frequencies of adsorbed species at 3075-3300 cm À1 are by about 1000 cm À1 lower than in the free hydrogen molecules. This indicates unusually strong perturbation of adsorbed hydrogen by reduced Cu þ1 ions that has been never before reported neither for hydrogen nor for adsorption o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Recent IR studies on hydrogen adsorbed in Cu−ZSM-5 have revealed rather low absorption frequencies at about 3070 and 3125 cm -1 assigned to the intramolecular stretching mode of hydrogen molecules interacting with a Cu(I)-ion, coordinated to the oxygens of an AlO 4 - tetrahedron. DFT calculations 12,15 on related model systems indicate a strong interaction between the hydrogen molecule and the Cu + ion and the formation of an η 2 -complex with a H−H separation of 0.82 Å, which gives a calculated red shift of the H−H stretching mode very close to the experimentally observed values.…”
mentioning
confidence: 99%
“…Recent IR studies on hydrogen adsorbed in Cu−ZSM-5 have revealed rather low absorption frequencies at about 3070 and 3125 cm -1 assigned to the intramolecular stretching mode of hydrogen molecules interacting with a Cu(I)-ion, coordinated to the oxygens of an AlO 4 - tetrahedron. DFT calculations 12,15 on related model systems indicate a strong interaction between the hydrogen molecule and the Cu + ion and the formation of an η 2 -complex with a H−H separation of 0.82 Å, which gives a calculated red shift of the H−H stretching mode very close to the experimentally observed values.…”
mentioning
confidence: 99%
“…The feasibility of this method of storage is basically ruled by the interaction between H 2 and the host material; therefore, the understanding of this interaction is crucial to infer the potential of different materials as storage media. With this objective, several experimental studies on the H 2 interaction with diverse zeolites have been reported in the last years [10,[12][13][14][15][16][17][18][19][20][21][22][23][24][25], focused mainly on the estimation of adsorption enthalpies by means of variable-temperature infrared spectroscopy [26,27]. A summary of the data obtained in these experimental works is presented in Table 1, where it is worth noticing that beside the structural properties of the various studied zeolites (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Since it has been revealed that Cu (I) sites in zeolite ZSM-5 exhibits unusual ability to bind H 2 [1], the H 2 -Cu + interaction has been widely investigated. [2][3]4] Present work illustrates decomposition of the interaction energy between copper or silver cations and hydrogen molecule into meaningful components as well as important contributions to this interaction brought about by embedding in zeolitic framework. The role of zeolitic environment in modifying cationic properties and thus the electronic processes underlying hydrogen activation is explained by decomposing electron density flow between the molecule and the cationic site into independent electron transfer channels.…”
Section: Introductionmentioning
confidence: 93%